Parvoviruses cause nuclear envelope breakdown by activating key enzymes of mitosis. - Manvi Porwal (Public Library of Science (PLoS), 2013)
Disassembly of the nuclear lamina is essential in mitosis and apoptosis requiring multiple coordinated enzymatic activities in nucleus and cytoplasm. Activation and coordination of the different activities is poorly understood and moreover complicated as some factors translocate between cytoplasm and nucleus in preparatory phases. Here we used the ability of parvoviruses to induce nuclear membrane breakdown to understand the triggers of key mitotic enzymes. Nuclear envelope disintegration was shown upon infection, microinjection but also upon their application to permeabilized cells. The latter technique also showed that nuclear envelope disintegration was independent upon soluble cytoplasmic factors. Using time-lapse microscopy, we observed that nuclear disassembly exhibited mitosis-like kinetics and occurred suddenly, implying a catastrophic event irrespective of cell- or type of parvovirus used. Analyzing the order of the processes allowed us to propose a model starting with direct binding of parvoviruses to distinct proteins of the nuclear pore causing structural rearrangement of the parvoviruses. The resulting exposure of domains comprising amphipathic helices was required for nuclear envelope disintegration, which comprised disruption of inner and outer nuclear membrane as shown by electron microscopy. Consistent with Ca⁺⁺ efflux from the lumen between inner and outer nuclear membrane we found that Ca⁺⁺ was essential for nuclear disassembly by activating PKC. PKC activation then triggered activation of cdk-2, which became further activated by caspase-3. Collectively our study shows a unique interaction of a virus with the nuclear envelope, provides evidence that a nuclear pool of executing enzymes is sufficient for nuclear disassembly in quiescent cells, and demonstrates that nuclear disassembly can be uncoupled from initial phases of mitosis.